Natural products, PGC-1α, and Duchenne muscular dystrophy - Ipek Suntar; Antoni Sureda; Tarun Belwal; Ana Sanches Silva; Rosa Anna Vacca; Devesh Tewari; Eduardo Sobarzo-Sánchez; Seyed Fazel Nabavi; Samira Shirooie; Ahmad Reza Dehpour; Suowen Xu; Bahman Yousefi; et al. (Elsevier, 2020)
Peroxisome proliferator-activated receptor γ (PPARγ) is a transcriptional coactivator that binds to a diverse range of transcription factors. PPARγ coactivator 1 (PGC-1) coactivators possess an extensive range of biological effects in different tissues, and play a key part in the regulation of the oxidative metabolism, consequently modulating the production of reactive oxygen species, autophagy, and mitochondrial biogenesis. Owing to these findings, a large body of studies, aiming to establish the role of PGC-1 in the neuromuscular system, has shown that PGC-1 could be a promising target for therapies targeting neuromuscular diseases. Among these, some evidence has shown that various signaling pathways linked to PGC-1α are deregulated in muscular dystrophy, leading to a reduced capacity for mitochondrial oxidative phosphorylation and increased reactive oxygen species (ROS) production. In the light of these results, any intervention aimed at activating PGC-1 could contribute towards ameliorating the progression of muscular dystrophies. PGC-1α is influenced by different patho-physiological/pharmacological stimuli. Natural products have been reported to display modulatory effects on PPARγ activation with fewer side effects in comparison to synthetic drugs. Taken together, this review summarizes the current knowledge on Duchenne muscular dystrophy, focusing on the potential effects of natural compounds, acting as regulators of PGC-1α.